Merancang Pintu Pintar dengan Keamanan Multifungsi berbasis IC AT-Mega 328 - Oktafian, Aris; Desriyanti, Desriyanti; Vidyastari, Rhesma Intan (Universitas Hang Tuah, 2020)
The door is a field that facilitates circulation between spaces covered by walls as access in and out, but it also helps drain air into the house to get light from the sun. The role of the door is very important, the door is a means to get in and out of the room, the door is also a security pillar of the house, car, and so forth. Therefore removing the door is made with a good security system, for example made using quality materials. Based on the above background, a home security system through a door is needed, and therefore the owner is required to make a smart door using IC Atmega 328 as the main controller. The idea was titled